2019
DOI: 10.1021/acs.est.9b03265
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Composition and Volatility of Nucleated Particles from α-Pinene Oxidation between −50 °C and +25 °C

Abstract: We use the thermal desorption profile of the detected condensed phase compounds in the FIGAERO-CIMS to estimate the vapor pressure. We correlate the temperature of the maximum signal in the thermogram (1/Tmax, in 1/K) to the vapor pressure of several known organic acids by manually depositing an aliquot of a mixture of the acids using a micro syringe. The mixture was dissolved in ethanol and went through the same thermo-desorption program that is applied to the actual measurements. Table S1 summarizes the satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 45 publications
3
43
1
Order By: Relevance
“…This is probably because of their very low concentrations and the difficulty to distinguish between real particle signal and background. We conjecture that especially at low temperatures this issue might be related to the fact that at lower temperatures, the autoxidation process to form HOMs is slower; therefore, the oxygen content and O : C decrease (Stolzenburg et al, 2018;Ye et al, 2019;Simon et al, 2020). The low contribution of these compounds in the gas phase might be reflected in the particle phase.…”
Section: Influence Of Relative Humidity On α-Pinene System At −50 • Cmentioning
confidence: 96%
See 1 more Smart Citation
“…This is probably because of their very low concentrations and the difficulty to distinguish between real particle signal and background. We conjecture that especially at low temperatures this issue might be related to the fact that at lower temperatures, the autoxidation process to form HOMs is slower; therefore, the oxygen content and O : C decrease (Stolzenburg et al, 2018;Ye et al, 2019;Simon et al, 2020). The low contribution of these compounds in the gas phase might be reflected in the particle phase.…”
Section: Influence Of Relative Humidity On α-Pinene System At −50 • Cmentioning
confidence: 96%
“…For instance, Kristensen et al (2017), measuring at −15 and +20 • C, showed an increased contribution of less oxygenated species to α-pinene SOA particles formed from ozonolysis at sub-zero temperatures. Ye et al (2019) measured the particle-phase chemical composition from α-pinene oxidation between −50 and +25 • C with the FIGAERO inlet (Lopez-Hilfiker et al, 2014). They found that during new particle formation from α-pinene oxidation, gas-phase chemistry directly determines the composition of the condensed phase.…”
Section: Introductionmentioning
confidence: 99%
“…S1); otherwise, the nitrate ionization scheme cannot fully detect them. The unimolecular reaction of the RO q 2 radicals proceeds at much slower rates at low temperatures, due to the height of the reaction barrier, while the bimolecular termination of the radicals is much less affected by the temperature (Ziemann and Atkinson, 2012;Frege et al, 2018). Therefore, at low temperatures, there is a higher chance that an RO q 2 radical will be lost before it reaches a high oxygenation level and forms a HOM that can be detected by the nitrate CI-APi-TOF.…”
Section: Effect Of Temperature On α-Pinene Oxidation and Hom Formationmentioning
confidence: 99%
“…On the other hand, lower temperatures lead to decreased autooxidation reaction rates and reduced yields of HOM. Recent studies have shown that the former effect compensates for the latter effect, having an overall increase in nucleation and growth rates at lower temperatures (Stolzenburg et al, 2018;Simon et al, 2020;Ye et al, 2019). While these mechanisms are clear in chamber studies, the situation becomes more complicated in the atmosphere because of the complexity of the atmosphere-biosphere system having simultaneous temperature-dependent processes that can enhance or suppress NPF, making current atmospheric observations inconsistent on the role of temperature on NPF (Kerminen et al, 2018).…”
Section: The Driving Atmospheric Parameters Of the Npf Eventsmentioning
confidence: 99%